Phenomena of Digital-Based Learning Media in the Indonesian Educational Curriculum (Kurikulum Merdeka) Regarding Chemical Bonding Materials: A Literature Review - Hayuni Retno Widarti; Antuni Wiyarsi; Sri Yamtinah; Ginesia Dudin Wijaya; Deni Ainur Rokhim (Universitas Sebelas Maret, 2024)
Chemistry is a subject with complex, abstract and microscopic concepts, so the quality of education must continue to be improved in line with developments in existing science. One of the realizations of this is the Indonesian Independent Curriculum (Kurikulum Merdeka). This curriculum aims to form a generation that is quick and responsive in understanding the material by being actively collaborative and communicative with various learning sources. One example of material that requires explicit delivery is chemical bonds, so the solution is to pay attention to supporting materials in learning such as learning media. This study aims to describe the phenomenon of digital learning media in the Indonesian Independent Curriculum (Kurikulum Merdeka) on chemical bonding concept The method used in this research is a systematic literature review for data collection. In this research, there are 12 literature indexed by Sinta on the topic of development and implementation of digital media in teaching the concept of chemical bonds. The research articles obtained were then examined connect the aims, methods and results of the research. Based on the literature review, it was found that there was a positive response from students and teachers in using digital learning media for the concept of chemical bonds